Does government incentive influence compliance behavior of business zakat among owners of SMEs?: an evidence via rasch measurement model / Mohd Rahim Khamis, Nazlinda Abdullah and Shereen Noranee. - Khamis, Mohd Rahim; Abdullah, Nazlinda; Noranee, Sheeren (Universiti Teknologi MARA Cawangan Selangor, 2016)
Government incentive is one of the significant factors that influence the compliance behavior of zakat. However, studies which have focused on government incentive such as zakat deduction and compliance behavior of zakat particularly in business zakat scenario is only next to inexistence. Therefore, this study aims to investigate whether the government incentives influence compliance behavior of business zakat among owners of SMEs.A total of 276 questionnaires collected from Small and Medium Entrepreneurs (SMEs) in Selangor and were analyzed using Rasch Measurement Model. The construct is found reliable with Cronbach Alpha of 0.60, person reliability index at 0.65 and item reliability index at 0.98. The statistical indicators such as mean square (MNSQ), Z-standardized (ZSTD), point measure correlation (PtMeaCorr) and Person Item Distribution Map (PIDM) revealed that out of the 247 respondents, 107 respondents (43.3%) who comply with business zakat payment were influenced by government incentives and 140 respondents (56.7%) who did not comply with business zakat payment probably are not influenced by government incentives. The finding of his study implies the significance of Rasch Measurement Model in explaining the compliance behavior of zakat among SMEs. Specifically, this study finds that government incentive is not influence the decision of owners on SMEs community to comply with business zakat payment.